Vegetation assessment of Awat-Awat Mangrove Forest, Sarawak, Malaysia - Arianto, Chandra Iman (Forestry Department Peninsular Malaysia, 2014)
Although mangroves provide a multitude of ecological and socio-economic services in Southeast Asia, they are still vulnerable to threats especially land use change. This study was carried out to assess the vegetation of Awat-Awat Mangrove Forest in Sarawak, Malaysia. A total of sixteen families and twenty four species were identified with Rhizophora apiculata and Nypa fruticans being the most dominant species. The succession process was clearly seen happening in this mangrove forest where pioneer species especially from the families Avicenniaceae and Sonneratiaceae were being taken over by the Rhizophoraceae.